Bacillus thuringiensis and Bacillus weihenstephanensis Inhibit the Growth of Phytopathogenic Verticillium Species - Hollensteiner, Jacqueline; Wemheuer, Franziska; Harting, Rebekka; Kolarzyk, Anna M.; Diaz Valerio, Stefani M.; Poehlein, Anja; Brzuszkiewicz, Elzbieta B.; Nesemann, Kai; Braus-Stromeyer, Susanna A.; Braus, Gerhard H.; Daniel, Rolf; Liesegang, Heiko (Frontiers in Microbiology, 2017)
Verticillium wilt causes severe yield losses in a broad range of economically important crops worldwide. As many soil fumigants have a severe environmental impact, new biocontrol strategies are needed. Members of the genus Bacillus are known as plant growth-promoting bacteria as well as biocontrol agents of pests and diseases. In this study, we isolated 267 Bacillus strains from root-associated soil of field-grown tomato plants. We evaluated the antifungal potential of 20 phenotypically diverse strains according to their antagonistic activity against the two phytopathogenic fungi Verticillium dahliae and V. longisporum. In addition, the 20 strains were sequenced and phylogenetically characterized by multi-locus sequence typing resulting in 7 different B. thuringiensis and 13 B. weihenstephanensis strains. All B. thuringiensis isolates inhibited in vitro the tomato pathogen V. dahliae JR2, but had only low efficacy against the tomato-foreign pathogen V. longisporum 43. All B. weihenstephanensis isolates exhibited no fungicidal activity whereas three B. weihenstephanensis isolates showed antagonistic effects on both phytopathogens. These strains had a rhizoid colony morphology, which has not been described for B. weihenstephanensis strains previously. Genome analysis of all isolates revealed putative genes encoding fungicidal substances and resulted in identification of 304 secondary metabolite gene clusters including 101 non-ribosomal polypeptide synthetases and 203 ribosomal-synthesized and post-translationally modified peptides. All genomes encoded genes for the synthesis of the antifungal siderophore bacillibactin. In the genome of one B. thuringiensis strain, a gene cluster for zwittermicin A was detected. Isolates which either exhibited an inhibitory or an interfering effect on the growth of the phytopathogens carried one or two genes encoding putative mycolitic chitinases, which might contribute to antifungal activities. This indicates that chitinases contribute to antifungal activities. The present study identified B. thuringiensis isolates from tomato roots which exhibited in vitro antifungal activity against Verticillium species.